2021
DOI: 10.3389/fendo.2021.758206
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles and Therapeutic Potential of Extracellular Vesicles in Infertility

Abstract: Infertility is becoming much more common and affects more couples. The past years witnessed the rapid development of the diagnosis and treatment upon infertility, which give numerous coupled more opportunities become parents. Extracellular vesicles are known as nano-sized membrane vesicles to play a major role in intracellular communication. In recent years, several basic and clinical studies have tried to investigate the correlation between the reproductive health/disorder and extracellular vesicles. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) (1,2) is widely defined as a kind of endocrine and metabolic disorder with a combination of signs and symptoms of androgen excess (hirsutism and/or hyperandrogenemia) and ovarian dysfunction (oligo-ovulation and/or polycystic ovarian morphology (PCOM)) (3). It was reported that the prevalence of PCOS in premenopausal women is up to almost 20% as the current, more inclusive definitions (4)(5)(6), which suggesting PCOS the most common endocrine and metabolic disorder in women at reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) (1,2) is widely defined as a kind of endocrine and metabolic disorder with a combination of signs and symptoms of androgen excess (hirsutism and/or hyperandrogenemia) and ovarian dysfunction (oligo-ovulation and/or polycystic ovarian morphology (PCOM)) (3). It was reported that the prevalence of PCOS in premenopausal women is up to almost 20% as the current, more inclusive definitions (4)(5)(6), which suggesting PCOS the most common endocrine and metabolic disorder in women at reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are particles derived from diverse types of cells [15], containing diverse cargos [16,17]. EVs could play roles in the cell communications and complicated interplay during the biological processes[18] and the pathological processes [19]. It was widely reported that extracellular vesicles could exert in cell proliferation [20], wound healing, drug resistance and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is a disease of the male or female reproductive system that results in failure to conceive after 12 months or longer of natural fertilization ( 10 ). According to estimates by the World Health Organization, about one in six couples of reproductive age worldwide may need assisted reproductive technology (ART) due to fertility problems ( 10 , 11 ). ART, including in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI), has been widely used among infertility patients ( 12 ).…”
Section: Introductionmentioning
confidence: 99%